FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PEMILIK USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (Studi pada Wajib Pajak Pemilik UMKM Di KPP Pratama Malang Selatan) - Pamuji, Adi Ratno (Jurnal Mahasiswa Perpajakan, 2014)
This research is based on the way of Government in giving facilitation to people regarding the implementation of tax obligation by establishing Government Regulation No. 46 2013. This research is purposed to explain influence variable of tax understanding, controlling, and Socialization significantly influence in taxpayers compliance. Research method that is used is explanatory research with quantitative approach. Data collection method by using questionnaire for 100 MSME owners who are registered in tax office pratama malang selatan. Using descriptive analysis and multiple linear regression helped by SPSS software version 21, this study showed that the variable tax understanding, controlling, and Socialization significantly influence in taxpayers compliance. Keywords: TaxÂ  Understanding, Controlling, Socialization, and Taxpayer Compliance